2016
DOI: 10.1177/2158244016631798
|View full text |Cite
|
Sign up to set email alerts
|

Fitness, Balance Efficacy, and Postural Control in Community-Dwelling Older Adults

Abstract: Age-related declines in postural control and physical fitness are strong risk factors for falls in older adults. Balance efficacy has been utilized to identify poor postural control, reduced physical function, and fall risk. However, it is not clear as to whether balance efficacy is truly a better predictor of functional fitness outcomes or postural control. Distinguishing these associations is an important step in the future derivation of physiotherapeutic programming to remediate acute and chronic decline. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Conversely, if a person reports low falls self-efficacy, their eyes open balance will be lower. This finding is in line with previous research (Kamide et al, 2019;Lee et al, 2016;Pua et al, 2017;Schepens et al, 2012) indicating that psychological states strongly affect physiological outcomes. Additionally, in line with research done by Tinetti et al (1994) and Vellas et al (1997), after a person falls, their fear of falling grows, which can cause them to live more cautiously, more sedentarily.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, if a person reports low falls self-efficacy, their eyes open balance will be lower. This finding is in line with previous research (Kamide et al, 2019;Lee et al, 2016;Pua et al, 2017;Schepens et al, 2012) indicating that psychological states strongly affect physiological outcomes. Additionally, in line with research done by Tinetti et al (1994) and Vellas et al (1997), after a person falls, their fear of falling grows, which can cause them to live more cautiously, more sedentarily.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, for the elderly, the vertical jump has been shown to be a good predictor of functional capacity ( Pijnappels et al, 2008 ), and risk of falling ( Lee, Biggan & Ray, 2016 ). It has been previously shown that loss of functional capacity interferes with the performance of activities of daily living (ADL) ( Foldvari et al, 2000 ; Macaluso & De Vito, 2004 ; Farias et al, 2013 ), decreasing the independence in ADL, and also increasing the prevalence of falls ( Lee, Biggan & Ray, 2016 ; Vieira et al, 2013 ). Therefore, it is reasonable to highlight that the vertical jump can be one of the most appropriate, useful, and suitable tests to evaluate the functional capacity of elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we believe that our results are clinically significant as it adds further and deeper understanding of the vestibular influence on a commonly performed daily function like sitto-stand could make test like timed up-and-go test and 30-second sitto-stand test more potentially useful in clinical decision making. Clinicians could benefit from an in-depth and feasible analysis of the role of vestibular inputs during sit-to-stand and what they expect from their patients as elderly or patients with balance disorders [2,15] which could help researchers and clinicians determine the root cause of functional limitations to develop more effective assessment and interventions.…”
Section: Resultsmentioning
confidence: 99%